Recent Progress and Development Trend of Self-Sweeping Fiber Laser - Zuo, Zhenzhong; Wang, Kaile; Chen, Haowei; Lu, Baole; Bai, Jintao (Frontiers in Physics, 2021)
Since 2011, when Kir'yanov et al. first reported a new wavelength self-sweeping ytterbium-doped fiber laser that does not rely on any tuning element but only on the dynamic induced grating generated in the gain fiber by the standing wave resonator structure, the self-sweeping effect based on fiber waveguides has been extensively studied, leading to great progress in fundamental physics and other applications of self-sweeping fiber lasers. Different doped fiber lasers have not only achieved the self-sweeping effect, but also observed new phenomena such as anomalous self-sweeping and continuous pulses. Due to their remarkable spectral and pulsed characteristics, self-sweeping fiber lasers have been widely used in spectral detection, fiber sensing and short pulse synthesis. In this paper, we will introduce the classification of different doped self-sweeping fiber lasers, summarize their different implementations, and introduce their self-sweeping laws, pulse characteristics, recent progress of applications and future development prospects.